ANALYSIS OF FLOUTING AND VIOLATING TOWARDS MAXIM OF QUALITY IN MY SISTER’S KEEPER NOVEL - Noertjahjo, Ester; Arifin, M Bahri; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
ABSTRACT The objectives of this research was to find the expression of flouting and violating towards maxim of quality in My Sister’s Keeper novel through major characters’ utterances and also to find the purposes of using flouting and violating toward maxim of quality. This analysis includes to descriptive qualitative method. This researcher used My Sister’s Keeper novel as the source of data. The data derived from the utterances of major characters containing the elements of flouting and violating towards maxim of quality. From the finding of this analysis, the elements of flouting and violating towards maxim of quality were found in major characters’ utterances through five strategies. They are hyperbole strategy, metaphor strategy, irony strategy, banter strategy, and lie strategy. Metaphor strategy was often used by major characters in this novel. It occurred because through metaphor strategy the characters can emphasize the point of talk to express their opinion clearly. From the analysis of five strategies, it found that there are seven purposes of using flouting and violating towards maxim of quality. Key words:    Flouting the maxim of quality, violating towards maxim of quality, purpose, My Sister’s Keeper ABSTRAK  Tujuan dari penelitian ini adalah menemukan ucapan dari penyimpangan dan pelanggaran terhadap maksim kualitas dalam novel My Sister's Keeper melalui ujaran karakter utama dan juga menemukan tujuan dari penggunaan penyimpangan dan pelanggaran terhadap maksim kualitas. Analisis ini termasuk dalam metode deskriptif kualitatif. Peneliti ini menggunakan novel My Sister's Keeper sebagai sumber data. Data berasal dari ujaran karakter utama yang mengandung unsur-unsur penyimpangan dan pelanggaran terhadap maksim kualitas. Dari analisis ini, unsur-unsur penyimpangan dan pelanggaran terhadap maksim kualitas ditemukan dalam ujaran karakter utama melalui lima strategi. Diantaranya adalah strategi hiperbola, strategi metafora, strategi ironi, strategi banter, dan strategi kebohongan. Strategi metafora sering digunakan oleh tokoh utama dalam novel ini. Itu terjadi karena melalui strategi metafora para tokoh dapat menekankan poin pembicaraan untuk mengekspresikan pendapat mereka dengan jelas. Dari analisis lima strategi tersebut, ditemukan bahwa terdapat tujuh tujuan dalam penggunaan penyimpangan dan pelanggaran terhadap maksim kualitas.Kata kunci:     Penyimpangan maksim kualitas, Pelanggaran maksim kualitas, Tujuan, My Sister’s Keeper